PEMBERIAN TERAPI CERMIN DALAM PENURUNAN INTENSITAS NYERI PADA IBU INPARTU KALA II - Nicky Danur Jayanti (LPPMK STIKES Widyagama Husada, 2013)
In this era a lot about the world of medical research scientist with mirror therapy. This therapy can be used as a way to reduce the pain, as if the brain can predict patient back to health and recovery from illness. While in the case of childbirth mirror therapy was able to show the real state of the baby's position visually in women who are doing labor that affect the growth of maternal motivation in making an effort to push aside the pain. Measurements conducted on 20 mothers pain when the second stage, when the mother was taught to push 5 times the mother is not able to properly push past the pain scale assessment after mirror therapy treatment is done with mirrors placed with the length and width of 10 cm. After that led her to see the state of the baby until the mother found the concentration point and will reach very high concentrations and the mother's mind is influenced by the image of the mirror so she has a very strong suggestion. Results before the mirror therapy is given is 18 respondents (90%) with severe pain, whereas pain was only 2 respondents (10%). Having given moderate pain mirror therapy there were 16 respondents (20%), whereas severe pain a 4 respondents (20%). The data obtained were statistically analyzed by paired t test T-test using SPSS. Mirror therapy proven to be effective in reducing labor pain on stage II.